Subjective Duration Assessment: An Implicit Probe for Software Usability - Czerwinski, Mary; Horvitz, Eric; Cutrell, Ed (IHM-HCI 2001 Conference, 2001)
This paper explores a new approach to gauging users’ difficulties with tasks, interfaces, and situations we refer to as subjective duration assessment. The approach, leveraging a psychological finding identified nearly seventy-five years ago, centers on the use of time estimation to characterize performance. . The finding showed that when engaging tasks are interrupted, participants tend to overestimate how long those tasks take when compared to actual task times. Conversely, tasks that are completed tend to be underestimated in terms of the overall task times. We introduce a metric, named relative subjective duration (RSD) that provides a means for probing the difficulty that users have with performing tasks without requiring the questioning of users about the difficulty. RSD has several uses, including a probe for difficulty that bypasses the bias toward the positive end of the scale typically seen in user satisfaction ratings after software usability studies. We explored the value of time estimation as a metric for evaluating task performance in HCI. Our hypothesis was that the duration of activity on tasks that are halted before completion would be overestimated, because participants were not able to complete them on their own, while the duration of activity on tasks completed successfully would be underestimated. A user study of interaction with an Internet browser explored the efficacy of the metric. Our results show that within deployment constraints, RSD shows promise as a valuable tool for HCI research.